Development and evaluation of microfluidic device for the determination of organophosphorus pesticide incorporating monolith based immobilized AChE with spectrophotometric detection - Parawee Rattanakit (2018)
A spectrophotometric microfluidic bioreactor system is described for the determination of organophosphorus pesticides. The glass chip was designed and fabricated for in situ monolithic preparation and subsequently acetlycholineserase (AChE) immobilization via a covalent bonding method. The porous polymer monolith was prepared using glycidyl methacrylate, ethylenedimethacrylate and 2,2-dimethoxy-1,2-diphenylethan-1-one in binary porogenic solvents of cyclohexanol and dodecanol. The epoxide groups of monolith were reacted with ethylenediamine and gluteraldehyde to allow immobilization of the enzyme using their amine groups. Organophosphorus pesticides can be determined by measuring their inhibition effect on the enzyme AChE using Ellman's reaction. A linear relationship between the absorbance and percentage inhibitions was obtained over the concentration range of 0.25 to 2.50 mg L -1 paraoxon with a correlation coefficient (r 2 ) of 0.9974. The limit of detection (LOD) defined as 10% inhibition (I 10 ) was 0.17 mg L -1 for paraoxon. The relative standard deviations (RSD) of 1.0 mg L -1 paraoxon was 3.73% (n = 5). The proposed μFI system incorporates efficient enzyme immobilization and reduces reagent consumption and waste production and could thus be considered to be more environmentally friendly. © 2013 Copyright Taylor and Francis Group, LLC.